Gender Equality Strategy through Technology-Based Islamic Education in Matrilineal Minangkabau Society to Support SDGs - Aldi, Muhammad; Khairanis, Retisfa (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS), 2025)
Gender equality is one of the global issues that has received serious attention in the Sustainable Development Goals (SDGs) agenda. Achieving gender equality in Indonesia is still a problem, especially in areas with strong cultural traditions such as Minangkabau. The purpose of this study is to develop a strategy for promoting gender equality through technology-based Islamic education in the context of a matrilineal Minangkabau society in order to improve the achievement of the Sustainable Development Goals (SDGs), particularly the goal of gender equality. The method used was a literature study with a qualitative approach, where data were collected from various sources, such as academic journals, books and related reports. The analysis focused on identifying effective strategies to integrate technology and Islamic principles to support education in Minangkabau society. The results show that technology integration has the potential to improve the status of women in Minangkabau society, which has adopted the matrilineal system, in addition to improving women's access to education. Among the strategies discussed are the development of gender-responsive curricula, teacher training in the use of technology based on Islamic principles, and the promotion of digital literacy among women through e-learning programs. However, issues such as access to technology and a strong patriarchal culture require collaborative and contextualized efforts. It is expected that this study can provide practical guidance for policy makers and educators in Minangkabau to build a more inclusive education system that supports the SDGs.